Apropriação da libras por estudantes do curso de tradução e interpretação em libras/ língua portuguesa - Leite, Eloá de Lucca (Universidade Federal de São Carlos, 2020)
This work consists of the analyzes resulting from the Course Completion Work (TCC) of the Bachelor's degree in Translation and Interpretation in Libras / Portuguese. The research aimed to investigate the process of appropriation of the Brazilian Sign Language (Libras) by students of a Translation and Interpretation course in Portuguese / Libras (TILSP) at a federal university in the interior of the state of São Paulo. The research problematized the dilemmas of such a process by two specific aspects: 1) the entry of students in this course without the knowledge of sign language and 2) the need for appropriation and fluency in sign language for the further development of translation skills and interpretation in this language, focus of the training proposal of the course. For this purpose, the bibliographic study was carried out by means of research that dealt with this theme, to understand the field of study, namely: the training of sign language translators and interpreters. We conducted a qualitative field research with a descriptive proposal. For data collection, a semi-open and semi-lingual online questionnaire was formulated for students who had already attended at least two years of graduation. As the course investigated is four years, it is expected that the student already has knowledge and fluency in sign language. The relevance of this research instrument is understood as a space in which the subject can reflect on his practices and the researcher can use it as a means of appropriating knowledge announced by the participants that reflect data from the object of his investigation. The data were analyzed qualitatively based on studies of an anthropological nature in the field of deafness, articulating them with the fields of education and training of translators and interpreters. With the research, we promoted a reflection that brought novelties and accessibility strategies for better training aimed at students of bachelor's degrees in translation and interpretation of the linguistic pair, Libras / Portuguese Language.
Appropriation of libras by students of the translation course and interpretation in libras / portuguese language
Keywords: Ensino superior; Formação de tradutores e intérpretes; Libras; CIENCIAS HUMANAS